Glucosylation of smoke-derived volatiles in grapevine (vitis vinifera) is catalyzed by a promiscuous resveratrol/guaiacol glucosyltransferase - Haratl, Katja; Huang, Fong-Chin; Giri, Ashok P.; Franz-Oberdorf, Katrin; Frotscher, Johanna; Shao, Yang; Hoffmann, Thomas; Schwab, Wilfried (Journal of Agricultural and Food Chemistry, 2017)
Vinification of grapes (Vitis vinifera) exposed to forest fire smoke can yield unpalatable wine due to the presence of taint compounds from smoke and the release of smoke derived volatiles from their respective glycosides during the fermentation process or in-mouth during consumption. To identify glycosyltransferases (GTs) involved in the formation of glycosidically bound smoke-derived volatiles we performed gene expression analysis of candidate GTs in different grapevine tissues. Second, substrates derived from bushfire smoke or naturally occurring in grapes were screened with the candidate recombinant GTs. A resveratrol GT (UGT72B27) gene, highly expressed in grapevine leaves and berries was identified to be responsible for the production of the phenolic glucosides. UGT72B27 converted the stilbene trans-resveratrol mainly to the 3-O-glucoside. Kinetic analyses yielded specificity constants (k(cat)/K-m) of 114, 17, 9, 8, and 2 mM(-1) s(-1) for guaiacol, trans-resveratrol, syringol, methylsyringol, and methylguaiacol, respectively. This knowledge will help to design strategies for managing the risk of producing smoke-affected wines.